The Impact of Age on Breast Cancer Incidence Among Libyan Women: A Meta-Analysis. - Ashleik, Naeima; Ben-Farag, Suaad; N. El-Saeiti, Intesar (Scientific Journal of University of Benghazi, 2025)
This meta-analysis, which draws on eight original studies, looks at the average age of Libyan women diagnosed with breast cancer. A full review of the original articles published in English between October 2016 and August 2024. A systematic review of five main databases was conducted to identify studies including Embase, Scopus, PubMed, Google Scholar and Web of Science. Only studies with unambiguous age data were included, as determined by the Population, Exposure, Comparator, Outcome, and Study Design (PECOS) criteria. The effect sizes were pooled using a random-effects model, and heterogeneity was measured with Cochran’s Q and I² statistics. The pooled mean age across studies was 47.81 years (95% CI: 46.87–48.74), indicating high variability (I² = 98.1%). Influence diagnostics identified one outlier study that contributed to the high heterogeneity. These findings highlight age distribution patterns in breast cancer cases in Libya, suggesting avenues for targeted early intervention strategies. Overall, these findings emphasize the demand for age-specific screening programs in Libya.